2001
DOI: 10.1053/euje.2000.0051
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Grafting in Patients with Severe Left Ventricular Dysfunction: Predictive Significance of Left Ventricular Diastolic Filling Pattern

Abstract: In patients with severe LV dysfunction undergoing CABG, impaired relaxation and pseudonormal pattern of LV diastolic filling correlated with postoperative improvement in LV regional contraction, while restrictive pattern correlated with high early postoperative mortality, morbidity and minimal improvement in LV systolic function. Restrictive LV filling pattern, early diastolic filling deceleration time and LV end-diastolic diameter were found to be independent predictors of perioperative mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…The clinical impact of preoperative left ventricular (LV) [1][2][3][4][5] and right ventricular (RV) 4,6 diastolic dysfunction on perioperative morbidity and mortality is increasingly recognized. The presence of severe LV diastolic dysfunction is associated with hemodynamic instability after cardiopulmonary bypass (CPB) and has been correlated with postoperative cardiac events 1 yr after coronary artery bypass graft (CABG) surgery.…”
Section: Résumémentioning
confidence: 99%
“…The clinical impact of preoperative left ventricular (LV) [1][2][3][4][5] and right ventricular (RV) 4,6 diastolic dysfunction on perioperative morbidity and mortality is increasingly recognized. The presence of severe LV diastolic dysfunction is associated with hemodynamic instability after cardiopulmonary bypass (CPB) and has been correlated with postoperative cardiac events 1 yr after coronary artery bypass graft (CABG) surgery.…”
Section: Résumémentioning
confidence: 99%
“…This problem is illustrated by existing studies. Vaskelyte et al [29], using our original definition for restrictive filling, reported that in patients with LVEF ≤ 35% a restrictive pattern (E/A ≥ 2 or an E/A ratio between 1 and 2 with a deceleration time b 150 ms) correlated with high early postoperative mortality, morbidity and minimal improvement in LV systolic function. Several other authors, including as previously mentioned Poulsen et al, have defined restrictive LV filling as a deceleration time b 140 ms independent of age [11].…”
Section: Covariatementioning
confidence: 99%
“…Prognostic value of the LV diastolic filling pattern has been already demonstrated in patients with CAD, undergoing CABG. 25 Our previous study revealed that restrictive LV diastolic filling is the marker of poor prognosis in patients with low LV EF undergoing CABG, as the postoperative complication rate (55.5%) and the perioperative mortality rate (33%) were highest in the restriction group. Furthermore, LV diastolic dysfunction was proved to be more sensitive than LV sys-tolic dysfunction (decreased LV EF) in predicting cardiac events after CABG.…”
Section: Discussionmentioning
confidence: 87%